A dynamic multiyear algorithm for transmission expansion planning including the computation of long term marginal prices - João Tomé Saraiva (2004)
Although electricity markets have a clear short-term accent, long-term expansion planning issues mustnt be forgotten namely if the current security of supply and quality of service levels are to be maintained. In view of this concern, this paper presents a model for expansion transmission planning together with the computation of the adequate long term marginal prices so that the marginal remuneration recovered along the planning period meets as much as possible the operation plus investment costs. The optimization model is solved using Simulated Annealing, given its ability to address discrete problems as the one in analysis. The model and the algorithm are tested using a case study based on the 400 / 220 /150 kV Portuguese transmission network considering a 6-year planning horizon as determined by current regulations.